2014
DOI: 10.3390/min4010074
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicles as a Novel Strategy for Shedding Encrusted Cell Surfaces

Abstract: Surface encrustation by minerals, which impedes cellular metabolism, is a potential hazard for microbes. The reduction of U(VI) to U(IV) by Shewanella oneidensis strain MR-1 leads to the precipitation of the mineral uraninite, as well as a non-crystalline U(IV) product. The wild-type (WT) strain can produce extracellular polymeric substances (EPS), prompting precipitation of U some distance from the cells and precluding encrustation. Using cryo-transmission electron microscopy and scanning transmission X-ray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Makarova et al 33 demonstrated that metal oxidation reactions, particularly with Fe, ultimately denature S-layer proteins. Membrane vesicle release may therefore be seen as an attempt by Sulfolobus cells to eliminate damaged S-layer proteins in order to enable replacement with new proteins (not associated with minerals), in a manner similar to that seen in organisms lacking S-layers for elimination of denatured or mineral-associated cell wall components 45 46 . Based on our present results, this issue of cell viability and response to stress upon passive Fe biomineralization would deserve a dedicated study.…”
Section: Discussionmentioning
confidence: 99%
“…Makarova et al 33 demonstrated that metal oxidation reactions, particularly with Fe, ultimately denature S-layer proteins. Membrane vesicle release may therefore be seen as an attempt by Sulfolobus cells to eliminate damaged S-layer proteins in order to enable replacement with new proteins (not associated with minerals), in a manner similar to that seen in organisms lacking S-layers for elimination of denatured or mineral-associated cell wall components 45 46 . Based on our present results, this issue of cell viability and response to stress upon passive Fe biomineralization would deserve a dedicated study.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, vesiculation functions as an envelope stress response, and increasing OMV production aids in bacterial survival under stress conditions 19,20,22,2427,42,75,76 (FIG. 3a, b).…”
Section: Omv Functions In Bacterial Physiologymentioning
confidence: 99%
“…This has been shown in stromatolites ( Decho et al, 2005 ) and in other systems, among which Fe cycling bacteria. For instance, EPS are produced by the Fe(III)-reducer Shewanella oneidensis promoting the precipitation of uraninite ( Shao et al, 2014 ) and by nitrate-dependent iron(II)-oxidizing bacteria precipitating Fe-oxyhydroxides or phosphates ( Miot et al, 2009b ; Klueglein et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, S. oneidensis was shown to form membrane vesicles that get mineralized when exposed to uranium, hence lessening cell surface mineralization ( Shao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%